Lethal lapses: How a positive interest rate shock might stress German life insurers - Mark Feodoria; Till Förstemann (Deutsche Bundesbank, 2015)
Life insurers typically grant policyholders a surrender option. We demonstrate that the resulting lapse risk could materialise in the form of a "policyholder run" if interest rates were to increase sharply. An inverse stress test based on a unique set of regulatory panel data suggests that German life insurers have become less resistant to an upward interest rate shock in the course of the financial and sovereign debt crisis from 2007 to 2011. Despite the challenges presented by the low-interestrate environment, the situation has not deteriorated since then. In light of the quantitative easing (QE) of monetary policy in the euro area, life insurers may find it difficult to continue this positive trend.
Keywords: G22; G33; C72; C13; 330; life insurance; interest rate risk; lapse risk; rational policyholder run; inverse stress test